ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
The Ross procedure is the only aortic valve replacement technique that restores long-term survival while maintaining quality-of-life. In the Ross procedure, the patient's own pulmonary valve is placed in aortic position, forming a pulmonary autograft. The main limitation of the intervention is postoperative dilatation under systemic blood pressures, compromising its durability. Existing polymer textiles can limit diameter expansion, but restrict physiological wall motion and cause vascular atrophy of the underlying tissue. Here, a mechanocompatible external support was developed and evaluated, stabilizing autograft diameter while preserving arterial compliance. Biodegradable tubular scaffolds were fabricated by electrospinning polycaprolactone and elastin polymer blends. As a preclinical proof-of-concept, supported and unsupported pulmonary arteries were transplanted into rats' abdominal aortas to mimic the mechano-biological conditions of the Ross procedure. Micro-computed tomography showed maintenance of wall diameter over eight weeks, whereas unsupported autografts exhibited significant dilatation. Histological analysis and mechanical testing highlighted benign adaptation in both the supported and unsupported autografts. A tailored degradation study further revealed how the physiological environment influences the mechanical integrity of the tissue-scaffold complex. Overall, the electrospun structures present a promising strategy to prevent dilatation while enabling autograft remodeling, offering a translational pathway to improve surgical outcomes in a cardiovascular context.